A comunicação da informação científica para popularização da ciência: proposta de documentário de divulgação científica para o Instituto Federal de Sergipe - Viard, Monique de Sá Tavares (2023)
This research addresses the importance of establishing the connection between Science and the adolescent public during the school years, enabling the formation of critical citizens and stimulating a greater interest in scientific research from an early age. Thus, this work uses the Federal Institute of Sergipe as a research field and the students belonging to the integrated high school as the target audience. Therefore, the objective of this research is to promote the culture of popularizing Science at the Federal Institute of Sergipe through the development of the documentary (product) “FIS is POP! Inclusion of youth through the Popularization of Science”, which presents concepts related to scientific diffusion as well as scientific research, giving voice to teachers, students, and one communication professional from the Institute. In this sense, this investigation is a Case Study focused on fostering actions that contribute to scientific dissemination within the institutional scope – specifically targeting students at the Aracaju Campus, located in the capital of Sergipe. Using a qualitative-quantitative approach, various data collection instruments were employed: interviews, questionnaires, focus group sessions, as well as bibliographic research in databases and documentary research. Qualitative data were analyzed from the perspective of Content Analysis, following Bardin’s methodology. Descriptive Statistics were used for the quantitative data, generating graphs and tables. After analyzing the collected data, it was found that young people have an interest in scientific research, Science, and Technology. However, they lack active search for topics, tools, and products related to the scientific field. Furthermore, through the applied questionnaire, it was determined that audiovisual format would be the most attractive for discussing science and scientific dissemination – which contributed to the development of the documentary. Thus, the results from the focus group with the students, after the product screening, demonstrate that issues such as timing, format, accessibility, among others, were addressed – making the product something that arouses interest and curiosity among the students of the integrated high school at FIS.